PERCEPTION OF NEUROMARKETING (International Journal of Food and Nutritional Sciences, 2022)
Neuromarketing helps to study how peoples brain react when they make purchase decision. The tools are FMRI, eye tracking, skin response etc. This paper focuses on Perception of Neuromarketing. The objective of this study was to find the factors influencing neuromarketing and to examine whether there exists any significant difference between demographic profile and perception of neuromarketing. For the purpose of study, we used questionnaire method to collect data. Consumers have positive attitude towards neuromarketing but the concept of neuromarketing is not well known to all category of people. The companies and marketers can increase the awareness about neuromarketing concept among consumers. And people who knew about the neuromarketing techniques feels that if marketers are going to use it in an ethical way they could derive more benefit out of neuromarketing techniques.